Exploring the influence of situational interest on outdoor tourists’ hedonic and eudaimonic well-being - Xu, Peng (Frontiers in Psychology, 2025)
IntroductionThis study introduces situational interest as a new factor influencing both hedonic and eudaimonic well-being in outdoor tourism settings. It explores how different dimensions of situational interest drive well-being and the mediation mechanisms involved.MethodsData were collected from 642 respondents through an online self-report questionnaire on the Credamo platform. Structural equation modeling was used to analyze the relationships between situational interest dimensions, well-being outcomes, and mediating factors.ResultsThe results show that instant enjoyment directly enhances hedonic well-being. Novelty has a direct effect on hedonic well-being and an indirect effect on eudaimonic well-being. Attention demand influences hedonic well-being both directly and indirectly. Challenge and exploration intention indirectly promote eudaimonic well-being through the satisfaction of autonomy needs.DiscussionBy uncovering the distinct pathways through which situational interest affects well-being, this study deepens our understanding of how outdoor tourism experiences can foster both immediate enjoyment and long-term personal growth. These findings provide practical insights for designing tourism activities that enhance tourists’ overall well-being.